2010
DOI: 10.1182/blood-2009-08-239004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biotinylation of the vasculature in B-cell lymphoma identifies BST-2 as a target for antibody-based therapy

Abstract: The discovery of accessible markers of lymphoma may facilitate the development of antibody-based therapeutic strategies. Here, we describe the results of a chemical proteomic study, based on the in vivo biotinylation of vascular proteins in lymphoma-bearing mice followed by mass spectrometric and bioinformatic analysis, to discover proteins expressed at the tissue-blood border of disseminated B-cell lymphoma. From a list of 58 proteins, which were more than 10-fold up-regulated in nodal and extranodal lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…The alternatively spliced domains extra domain A (EDA) and extra domain B (EDB) of fibronectin, which are targeted by the F8 and L19 antibodies, respectively, exhibit a high level of conservation among species and are virtually undetectable in normal tissues; however, they are abundantly expressed in the stroma and neovasculature of most aggressive types of human cancers 96,[102][103][104][105][106][107][108][109][110] . Similarly, systematic chemical proteomics studies 107,[111][112][113] have recently shown that another component of the extracellular matrix, periostin, exists in several splice isoforms that are abundantly found in most types of cancers [111][112][113][114] . 42,43 or using nanoparticles to design CAIs 44 .…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…The alternatively spliced domains extra domain A (EDA) and extra domain B (EDB) of fibronectin, which are targeted by the F8 and L19 antibodies, respectively, exhibit a high level of conservation among species and are virtually undetectable in normal tissues; however, they are abundantly expressed in the stroma and neovasculature of most aggressive types of human cancers 96,[102][103][104][105][106][107][108][109][110] . Similarly, systematic chemical proteomics studies 107,[111][112][113] have recently shown that another component of the extracellular matrix, periostin, exists in several splice isoforms that are abundantly found in most types of cancers [111][112][113][114] . 42,43 or using nanoparticles to design CAIs 44 .…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…In this case, vessel/blood radioactivity ratios may be predictive of the relative damage caused by a particles to endothelial cells and blood cells. immunohistochemistry), transcriptomic studies, in vivo phage library panning (44), and perfusion-based mass spectrometry-assisted techniques (45)(46)(47). We have developed human monoclonal antibodies (L19, F8, and F16) specific to splice isoforms of fibronectin and tenascin-C, which represent some of the most extensively characterized markers of tumor angiogenesis known so far (42).…”
Section: Vascular Tumor Targetingmentioning
confidence: 99%
“…Of interest, it was recently discovered that fibronectin and tenascin-C isoforms are abundant not only in the majority of solid tumors but also around the neovasculature of most lymphoma types (47,50,51). The L19 antibody in SIP format and labeled with 131 I has shown promising results for the radioimmunotherapy of refractory Hodgkin's lymphoma patients, and more than 100 cancer patients have already been treated with this agent (Fig.…”
Section: Identifymentioning
confidence: 99%
“…The resulting biotinylated proteins can then be easily recovered using streptavidin followed by on-resin proteolyitic digestion and HPLC and finally mass spectrometry to identify proteins assessable in the circulatory system. This technique led to the identification of BST-2 as a novel target for antibody-based therapy (Schliemann, Roesli et al 2010). Numerous proteomic techniques have been used over the years to discover new targets such as a phage display protocol where by mice are injected with a phage library and tissues excised and phage bound are identified (Pasqualini and Ruoslahti 1996).…”
Section: Novel Mab Therapeutics In Cancermentioning
confidence: 99%